Enforcing Military Discipline by Gaktib Koopsud II of the Indonesian Air Force: Legality and Accountability in Military Administrative Law - Herdi Mochammad Ramdhan; Ujuh Juhana (Green Social: International Journal of Law and Civil Affairs, 2026)
This article examines the enforcement of military discipline by the Order and Discipline Enforcement function (Gaktib) of Air Operations Command II of the Indonesian Air Force. It focuses on whether Gaktib authority is consistent with the principles of legality and accountability in Indonesian military administrative law. The study is important because the exercise of military authority must remain consistent with the rule of law while ensuring effective organizational discipline and operational readiness. Using normative juridical research, the article analyzes statutes, military regulations, legal doctrines, and conceptual principles concerning authority, discipline, due process, and command responsibility. The analysis shows that Gaktib is normatively authorized to conduct supervision, inspection, order enforcement, documentation, and reporting of alleged disciplinary violations, while the authority to impose disciplinary sanctions remains vested in the Commanding Officer Authorized to Punish. Although the existing framework generally satisfies legality and accountability requirements, clearer regulatory boundaries, stronger documentation, internal supervision, and professional training are necessary to prevent misinterpretation, improve institutional consistency, and strengthen rule-of-law-based military governance.